2019
DOI: 10.1016/j.ijfoodmicro.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced shelf-life of the formulated biocontrol agent Bacillus amyloliquefaciens CPA-8 combining diverse packaging strategies and storage conditions

Abstract: Two effective biocontrol products (named as BA3 and BA4) based on Bacillus amyloliquefaciens CPA-8 have been reported as a potential alternative to chemical applications against brown rot caused by Monilinia spp. on stone fruit. To have practical use, this study aimed to describe the best packaging strategies (bags or flasks, atmosphere, and temperature of storage) to not only guarantee efficacy but also stability and ease of application of the products to be handled through the normal channels of distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Both aforementioned BCAs have been studied extensively in relation to some of the major obstacles for their success as a commercial biocontrol product. These include the production of sufficient quantities of microorganisms to ensure optimum shelf life, 18 broadening the spectrum of action to a wider range of hosts, 11 and determining the responses to environmental stress under field conditions 19,20 . The results indicated that both BCAs are promising biocontrol products under commercial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Both aforementioned BCAs have been studied extensively in relation to some of the major obstacles for their success as a commercial biocontrol product. These include the production of sufficient quantities of microorganisms to ensure optimum shelf life, 18 broadening the spectrum of action to a wider range of hosts, 11 and determining the responses to environmental stress under field conditions 19,20 . The results indicated that both BCAs are promising biocontrol products under commercial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained information is essential when considering that not all BCAs can survive the conditions imposed during the formulation process at large‐scale production, even if in most cases protective substances are added to the formulation medium to improve the stability 32 . Additionally, the literature reported a strong effect of packaging (flasks versus bags) and storage conditions, especially temperature, on the shelf life of BCAs 33–36 . To exploit a BCA as a commercial product, important concentrations of microorganism biomass should be produced, stabilized, packaged and correctly stored/managed to be transported to its end‐user 32 .…”
Section: Resultsmentioning
confidence: 99%
“…32 Additionally, the literature reported a strong effect of packaging (flasks versus bags) and storage conditions, especially temperature, on the shelf life of BCAs. [33][34][35][36] To exploit a BCA as a commercial product, important concentrations of microorganism biomass should be produced, stabilized, packaged and correctly stored/managed to be transported to its end-user. 32 This is one of the reasons why their use is still limited and contains hurdles.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Bacillus species are also known to produce siderophore and volatile organic compounds (VOCs). VOCs are low molecular weight compounds that easily evaporates at normal temperature and pressure [17]. The effective components of VOCs varies between different strains.…”
Section: Discussionmentioning
confidence: 99%